Psychosocial characteristics and smoking behaviour in young Western Australian pregnant women at their first hospital appointment for pregnancy care. (August 2016) - Lewis, L.; Hauck, Y.L.; Ronchi, F.; Allsop, S.; Doherty, D.A.
Highlights: This study builds on the evidence around young Australian women who continue to smoke in pregnancy. Young pregnant smokers require assessment of illicit drug use, suicidal ideation and sexual abuse. It is important to tailor individual, woman centred approaches to promote smoking cessation.